Profil minat belajar siswa dalam pembelajaran daring - Indah Rosyidah Sodik; Anna Rufaidah; Susiati Susiati (Universitas Indraprasta PGRI, 2021)
The aimed of this study was to determine the profile of students' interest in learning in online learning during the pandemic and its implications for guidance and counseling services at SMA Islam As-Syafi'iyah 01. The approach used in this study was a descriptive quantitative approach. The research sample used the purposive sampling technique, which was 105 students of class XI SMA Islam As-Syafi'iyah. This research was conducted by distributing an instrument in the form of a learning interest questionnaire in online learning. Analysis of research data using descriptive statistics. The results of the study regarding the profile of learning interest indicate that interest in learning in online learning at SMA Islam As-Syafi'iyah is in the Medium category, which is 84%